Women resistance to early-age marriage in Wadon Ora Didol: Critical discourse analysis - Sintya, Dea Erma; Pratiwi, Rhesa Zuhriya Briyan (Universitas Padjadjaran, 2024)
Background: Wadon Ora Didol is a documentary film highlighting women’s resistance to the problem of early marriage. The rise of early marriage in Indramayu is a serious problem regarding the exploitation and objectification of women. This is actually related to the traditions and culture of Indramayu, thus, it is giving rise to a feminist-based resistance movement against these traditions. Purpose: This article aims to analyze and describe the resistance carried out by women against early-age marriage in the film Wadon Ora Didol through critical discourse analysis of Sara Mills. Methods: It uses a descriptive research approach, with primary data collection through documentation on selected scenes and relevant literature studies. Data findings were analyzed using theories of resistance and feminism. Results: There is women’s resistance in the film Wadon Ora Didol, which is identified through two positions: first, as the subject of resistance displayed by demonstrators and their efforts to revise laws of marriage; second, a slight object position through scenes showing the exploitation and objectification of women. Dominantly, Wadon Ora Didol proves that women are the main actors who are constructed to be able to fight, be independent, and be free to express and convey criticism of the problem of early-age marriage. This film also presents women who are responsive to caring about the fate of other women, both domestically and publicly, so that all individuals are equal and have their rights to freedom. Implications: These findings provide social criticism of the importance of women’s rights in society, as well as their struggle for existence in feminism. It is hoped that the results can provide other aspects to increase public awareness to be more responsive to social problems and exploitation of women, especially regarding early marriage.